Silicon Photonics Bloom - Boyraz, Ozdal; Zhao, Qiancheng (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The open access journal Micromachines invites manuscript submissions for the Special Issue "Silicon Photonics Bloom". The past two decades have witnessed a tremendous growth of silicon photonics. Lab-scale research on simple passive component designs is now being expanded by on-chip hybrid systems architectures. With the recent injection of government and private funding, we are living the 1980s of the electronic industry, when the first merchant foundries were established. Soon, we will see more and more merchant foundries proposing well-established electronic design tools, product development kits, and mature component libraries. The open access journal Micromachines invites the submission of manuscripts in the developing area of silicon photonics. The goal of this Special Issue is to highlight the recent developments in this cutting-edge technology.]